SHOWING AND ANALYZING OF THE IMAGE SCHEMAS ( KURDISH READING AND GRAMMAR BOOK OF SIXTH GRADE OF BASIC SCHOOL ) AS A SAMPLE - N. ABDULLAH, DR.ABDULSALAM (Journal of Duhok University, 2019)
The aim of this research is to show and analyze the image schemas in Kurdish reading and grammar book of sixth grade of basic school as an example in cognitive linguistics context. The Image schema is a main theme of Philosophy, Psychology, and linguistics in cognitive linguistics. The image schema has its own significance; therefore, image schemas as a process of thoughts and language can show the basic concepts and initial complexities in an organized way. So, this topic has its own significance in educational and learning fields especially in the fields which are related to language and thoughts.This research tries to get the Image schemas of containment schemas, path schemas, force schemas of johnson, such as basic schemas in Kurdish reading and grammar book of sixth grade of basic school.